Evaluability assessment of specialized dental care in Brazilian public health system (Research, Society and Development, 2022)
Evaluability Studies (ES) are pre-evaluative studies that precede the evaluation of a service. The objective of this study was to conduct an ES of secondary oral health care in Brazil, offered by the national public health system - SUS (Unified Health System) - through the Dental Specialty Centers (DSC). Nationally based study, carried out between the years 2017-2020, based on the system of Thurston e Ramaliu’s 7 elements. Twenty-nine members involved in the implementation and operation of the DSC participated in the study. The evaluation tool was validated in its content and appearance. Data were analyzed through the Content Validity Index (CVI) and according to the Content Analysis method. DSC description, based on documents and scientific evidence, allowed to understand its legal framework, operationalization, and main events that characterize it. The theoric-logic model defined 3 components to be evaluated: comprehensiveness health care, access to secondary oral health care and DSC management. The evaluation tool was validated in 2 rounds, with CVI>75%. The study demonstrated that secondary oral health care is evaluable and has a favorable scenario for its development. An inedited DSC questionnaire was established and validated.